Effects of an Oral Multi-vitamin Carbohydrate Beverage on Intraoperative Nausea and Vomiting in Women Converted from Vaginal Delivery to Cesarean Section - Jinli Xu; Minhong Shen; Jie Shen; Bing Han; Qin Huang; Youguo Chen (IMR Press, 2024)
Background: Nausea and vomiting are common and unpleasant symptoms for pregnant women during cesarean section, which can lead to aspiration, a serious complication that can cause pneumonia. This study aimed to evaluate the effects of oral multi-vitamin carbohydrate beverage on maternal intraoperative nausea and vomiting by gastric ultrasound. Methods: This was a single-center, randomized controlled trial. According to their diet, pregnant women who were converted from vaginal delivery to cesarean section were divided into two groups: the observation group (multi-vitamin carbohydrate beverage) or the control group (semi-solid food). The cross-sectional area (CSA) of the gastric antrum was measured by ultrasound before cesarean section, and the occurrence of intraoperative nausea, vomiting, and aspiration was recorded in both groups. Results: The CSA of the gastric antrum at 1 h, 2 h, after eating, and before cesarean section in the observation group was significantly smaller than that in the control group. This suggests that an oral multi-vitamin carbohydrate beverage needs less gastric emptying time. The incidence of vomiting in the observation group was significantly lower than that in the control group. Moreover, the pH of the vomited fluid in the observation group was higher than that in the control group, indicating that oral multi-vitamin carbohydrate beverage may reduce the acidity of stomach contents, which can further reduce the risk and severity of vomiting. Conclusions: Oral multi-vitamin carbohydrate beverage can promote gastric emptying and reduce the incidence and harm of vomiting during urgent cesarean section. This dietary intervention may be a simple and effective way to improve maternal outcomes during cesarean section. Clinical Trial Registration: The study has been registered on https://classic.clinicaltrials.gov/ (registration number: NCT06333626).